PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP KEPUTUSAN PENGGUNAAN BRIMO PADA NASABAH BANK BRI CABANG KAB. TANGERANG YANG DIMEDIASI OLEH KEPUASAN NASABAH - Nur Hendrawan; Fuad Mas’ud (UIN Sunan Kalijaga, 2023)
This study aims to analyze the effect of service quality and trust on usage decisions on BRImo services at the Branch Office. Tangerang Regency which is mediated by satisfaction. The research sampling used a purposive sampling method based on certain conditions, namely BRI customers at the Tangerang Regency Branch Office who had used BRImo services in the past month. The number of research samples selected was 303 respondents. Data was obtained through the distribution of questionnaires distributed online via google form with two parts. The first part contains questions related to the characteristics of the respondents. The second part contains statements to determine respondents' perceptions of service quality, trust, user satisfaction, and usage decisions. Data analysis using statistical testing through AMOS. The research data has met the criteria for Confirmatory Factor Analysis (CFA), normality, and Goodness of Fit (GoF). The results of the study successfully proved that service quality has a significant effect on satisfaction and usage decisions. Meanwhile, trust affects satisfaction, but trust statistically has no effect on usage decisions. Meanwhile, satisfaction statistically affects usage decisions. The mediation test results prove that satisfaction successfully mediates the relationship between service quality and usage decisions, and trust and usage decisions.